2013
DOI: 10.3109/14767058.2013.799657
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chorionicity and twin-to-twin delivery time interval on short-term outcome of the second twin

Abstract: Increasing delivery interval was associated with a significant decrease in pH and Apgar, but there was no difference between MC and DC twins. Low Apgar of the first twin increased the risk of second twin NICU admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
3
17
1
1
Order By: Relevance
“…However, some studies also support our findings that maternal age (Milsom et al, 2002) and BMI at birth (Kiran et al, 2005;Rode et al, 2005) are not associated with Apgar score. Monochorionicity was an important risk factor for adverse perinatal outcomes in twins (Dube et al, 2002;Hjorto et al, 2014;Lindroos et al, 2018; van Beijsterveldt et al, 2016), but was not associated with Apgar scores in our study.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…However, some studies also support our findings that maternal age (Milsom et al, 2002) and BMI at birth (Kiran et al, 2005;Rode et al, 2005) are not associated with Apgar score. Monochorionicity was an important risk factor for adverse perinatal outcomes in twins (Dube et al, 2002;Hjorto et al, 2014;Lindroos et al, 2018; van Beijsterveldt et al, 2016), but was not associated with Apgar scores in our study.…”
Section: Discussioncontrasting
confidence: 61%
“…A multiple pregnancy is a risk factor for adverse outcomes, including low Apgar scores (Morley et al, 1989;Pourali et al, 2016;Svenvik et al, 2015;Thorngren-Jerneck & Herbst, 2001). This holds specifically for MC pregnancies (Hjorto et al, 2014;Lindroos et al, 2018) and DC pregnancies with discordant fetal weight (Vulic et al, 2017). Again, some studies failed to find an association with chorionicity (Machado et al, 2017).…”
Section: Pregnancy Characteristicsmentioning
confidence: 99%
“…Vaginal delivered preterm MC second twin may be at an increased risk compared to DC preterm second twin, a difference that may diminishes towards term, as foetuses at risk are already sorted out (Joseph and Kramer 2017). A stated hypothesis is that the decrease in pH in MC second twin may exceed that of DC second twin, which was not confirmed in vaginally delivered twin pregnancies at term (Hjortø et al 2014). The aim of the present study was to investigate the effect of chorionicity on umbilical pH in relation to increasing twin-to-twin DTI from 30 weeks of gestation and compare the outcome before and after 34 weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Major available published studies have not discriminated between monochorionic (MC) and dichorionic (DC) vaginally delivered twins when examining the relationship between umbilical pH and twin-to-twin DTI. However, a recent study found no effect of chorionicity and twin-to-twin DTI on the short-term outcome of second twin after 36 weeks of gestation (Hjortø et al 2014). But there is a risk for substantial bias, as a higher incidence of complications during pregnancy are probably to be found in MC twins and the problematic ones are possibly selected for caesarean section (Ylilehto et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The present results are in agreement with several studies reporting that a longer time interval is related to a lower Apgar score at 1, 5, and 10 minutes, and a lower mean umbilical pH . An intertwin interval more than 30 minutes has also been associated with a worsening in arterial and venous umbilical cord pH, partial pressure of CO 2 , and base excess, leading to an increased risk of fetal distress and acidosis in the second twin …”
Section: Discussionmentioning
confidence: 99%